PENDAMPINGAN MASYARAKAT DALAM PEMBIASAAN HIDUP BERSIH DAN PENGELOLAAN SAMPAH SEBAGAI UPAYA PENINGKATAN KUALITAS LINGKUNGAN DI KOTA SERANG BANTEN - Mukhlis, Ahmad; Komarudin, Mochamad Fahru; Lesmana, Ihwan Satria; bahits, Abdul; Triana, Leni; Pebrianti, Pebrianti (Yayasan Education and Social Center, 2025)
This community service program aims to improve environmental quality through community assistance in fostering clean living habits and household waste management in Serang City, Banten Province. The main issues faced by the community include low environmental awareness, inconsistent clean living behavior, and suboptimal household waste management practices. The program was conducted for one month in August 2025 using participatory and educational approaches. The methods applied included socialization, training, hands-on assistance, and participatory evaluation. The target participants were households, with the involvement of community leaders and environmental cadres. The results indicate a significant increase in community knowledge and awareness regarding environmental cleanliness and responsible waste management. Behavioral changes were observed, including regular waste segregation, improved neighborhood cleanliness, and increased community participation in collective cleaning activities. The program also contributed to reduced waste accumulation and improved environmental conditions in residential areas. Furthermore, it strengthened social cohesion and collective responsibility for environmental sustainability. This community service activity is expected to serve as a sustainable model that can be replicated in other urban areas with similar characteristics.